Percutaneous endoscopic creation of a neoinfundibulum for a calyceal diverticulum: A case report and review of the literature - Das, Arighno; Blumenthal, Zoe; Monroe, Eric; Farhat, Walid A.; Bhatia, Vinaya P. (Frontiers in Urology, 2022)
Introduction Calyceal diverticula (CD) are cystic structures within the renal parenchyma that likely result from inappropriate interaction between the ureteric bud and metanephric blastema during development and, if obstructed, may cause problems that include flank pain, urinary tract infections, gross hematuria, or nephrolithiasis. Herein, we present the results of percutaneous management of an obstructed calyceal diverticulum causing recurrent flank pain and infections in a 17-year-old girl. Case summary The patient initially presented with febrile pyelonephritis, at which time an ultrasound was concerned about an abscess versus an infected cyst. She underwent percutaneous drain placement with IV antibiotics and improved. Three years later, she re-presented with similar symptoms. After a similar treatment course, a sinogram revealed communication of the cystic-appearing lesion with the proximal ureter, confirming a diagnosis of a calyceal diverticulum. The patient opted for endoscopic management. An initial attempt at ureteroscopy was unsuccessful due to both the small ureteral caliber as well as the stenotic infundibular os. A repeat attempt at percutaneous management revealed a stenotic infundibulum that could not accommodate a wire. A holmium laser fiber was used to create a neoinfundibulum from the diverticulum to the renal pelvis adjacent to the stenotic infundibular os. Follow-up retrograde pyelography and ultrasonography confirmed an interval decrease in size of the infundibulum, and the patient’s infectious symptoms and pain resolved. Discussion CD is a rare anomaly and is infrequently reported in the pediatric population. Percutaneous management of CD in adults has been well described in the literature. Direct percutaneous management of CD involves access to the CD and ablation of the CD cavity to prevent re-accumulation of urine. Previous studies done in adults have suggested that stone-free rates from this management range from about 80% to 100%. Diverticular obliteration, as measured by postoperative CT scans, also appears to be feasible in a percutaneous, antegrade approach, with complete diverticular obliteration rates ranging from 60% to 100%. Our case demonstrated a successful decrease in size from the original diverticulum (9 cm) to a smaller size (2 cm). Future studies with longer follow-ups will need to ascertain if percutaneous management of symptomatic CD is effective in the pediatric population.